The Closet in Sports - Wagner Xavier Camargo (Revista Estudos Feministas, 2018)
Recently there has been some controversy about sexualities and sexual practices of athletes in the professional world of sports. More than that, what has disturbed public opinion is the phenomenon of the homosexuality in sports toward the process of coming out. This article aims to analyze ethnographic data collected in LGBT+ (lesbian, gay, bisexual, transgender, others) sports championships, trying to observe how athletes’ speeches about their sexualities challenge a complex system of control (and self-control) of their own sexualities and of the others’ sexualities, building up a framework of references about the secret of the closet. Thinking over (homo)sexualities in these scenarios matter in sense that it poses, face to face, the fields of study of Gender and Sexuality at the intersection with the world of sports.